Pengaruh Budaya kerja dan lingkungan kerja terhadap kinerja pegawai pada Kantor Kementerian Agama Kabupaten Lamongan - Kulsum, Umu; Indrarini, Rachma (Universitas Negeri Surabaya, 2023)
This study aims to examine the effect of work culture and work environment to the employee performance at the Office of the Ministry of Religion of Lamongan Regency. This research was conducted using a quantitative approach. The number of samples used in the research were 71 respondents, which are all employees working at the Office of the Ministry of Religion of Lamongan Regency. This study used a questionnaire that was measured using a Likert Scale and analyzed using the SPSS program. Based on the results of testing the first (H1), second (H2) and third (H3) hypotheses, it shows that there is a significant influence between work culture and employee performance with a significance level of 0.016 (p <0.05) for the first hypothesis (H1), 0.000 (p<0.05) for the second hypothesis (H2) and 0.000 (0<0.05) for the third hypothesis (H3). Based on the F test also shows that the variables of work culture and work environment have an influence of 23.77% on employee performance. The results of the study show that work culture and work environment together have a significant effect on employee performance at the Office of the Ministry of Religion of Lamongan Regency.